Scale Development and Validation to Measure Occupational Health Literacy Among Thai Informal Workers - Weeraporn Suthakorn (2020)
© 2020 The Authors Background: The high incidence of work-related diseases and injuries among day-laborers and workers with no legal contracts (informal workers) has received the attention of the Thai authorities. Workers' low occupational health literacy (OHL) has been reasoned as one contributing factor. Absence of a valid tool has prevented assessment of informal workers' OHL. The aim of this study was to create a valid and reliable Occupational Health Literacy Scale within the context of Thai working culture (TOHLS-IF). Methods: This study used the mixed method approach to develop TOHLS-IF. Questions were generated using in-depth interviews and an extensive review of the literature. Experts' assessment confirmed the content validity of TOHLS-IF. The scales of its psychometric properties were assessed in a sample of 400 informal workers using cluster random sampling. Results: The final version of the TOHLS-IF comprises 38 items within 4 dimensions: Ability to Gain Access, Understanding, Evaluation, and Use of occupational health and safety information. Factor analysis identified items explaining 50.22% of the total variance. The final confirmatory analysis confirmed the model estimates were satisfactory for the construct. TOHLS-IF demonstrated a high internal consistency and satisfactory reliability (Cronbach's alpha = .98). Conclusion: The TOHLS-IF is a valid and reliable instrument to assess informal workers' OHL. The structural dimensions of this instrument are based on the concept of health literacy and Thai culture. Thai health professionals are encouraged to benefit from this instrument to assess their workers' OHL and apply findings as guidelines for effective occupational health and safety interventions.